Feminist methodology : challenges and choices - Ramazanoglu, Caroline, 1939- (Online access: SAGE SAGE Research Methods Core., 2002)
'Feminist Methodology' is an accessible demonstration of how feminist approaches to methodology engage with debate in Western philosophy to raise critical questions about knowledge production.